The case of the million-dollar mystery - Preller, James; Smith, Jamie; Alley, R. W. (Robert W.); Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2002)
"What's bright and shiny and hard to find? Buried treasure! Jigsaw's class finds a hidden riddle that leads them on a treasure hunt..."
"A Little Apple paperback."
G2
Keywords: Inventions -- Fiction; Detective and mystery stories; Children's stories; Mystery fiction